2015
DOI: 10.1155/2015/823026
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Analysis of a Nitrogen-Phosphorus-Phytoplankton Model

Abstract: This paper presents a nitrogen-phosphorus-phytoplankton model in a water ecosystem. The main aim of this research is to analyze the global system dynamics and to study the existence and stability of equilibria. It is shown that the phytoplankton-eradication equilibrium is globally asymptotically stable if the input nitrogen concentration is less than a certain threshold. However, the coexistence equilibrium is globally asymptotically stable as long as it exists. The system is uniformly persistent within thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In the absence of delay, theoretical analysis indicated that the unique positive equilibrium is globally asymptotically stable in model (1) if it exists. Deng et al [48] also studied a nitrogen-phosphorus-phytoplankton model without delay, where Holling II function was employed to describe the nutrient uptake dynamics of phytoplankton. Although the function modelling the nutrient uptake dynamics of phytoplankton is different, they get the same results.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of delay, theoretical analysis indicated that the unique positive equilibrium is globally asymptotically stable in model (1) if it exists. Deng et al [48] also studied a nitrogen-phosphorus-phytoplankton model without delay, where Holling II function was employed to describe the nutrient uptake dynamics of phytoplankton. Although the function modelling the nutrient uptake dynamics of phytoplankton is different, they get the same results.…”
Section: Discussionmentioning
confidence: 99%